Gastrin, Cholecystokinin, Signaling, and Biological Activities in Cellular Processes - Zeng, Qiang; Ou, Lei; Wang, Wei; Guo, Dong-Yu (Frontiers in Endocrinology, 2020)
The structurally-related peptides, gastrin and cholecystokinin (CCK), were originally discovered as humoral stimulants of gastric acid secretion and pancreatic enzyme release, respectively. With the aid of methodological advances in biochemistry, immunochemistry, and molecular biology in the past several decades, our concept of gastrin and CCK as simple gastrointestinal hormones have changed considerably. Extensive in vitro and in vivo studies have shown that gastrin and CCK also exert potent pro-proliferative and anti-apoptotic effects in several physiological processes including maintenance of gastric mucosa and pancreatic islet integrity, neurogenesis, and neoplastic transformation. Indeed, gastrin and CCK, as well as their receptors, are expressed in a variety of tumor cell lines, animal models, and human samples, and might contribute to certain carcinogenesis. In this review, we will briefly introduce the gastrin and CCK system and highlight the effects of gastrin and CCK in the regulation of cell proliferation and apoptosis in both normal and abnormal conditions. The potential imaging and therapeutic use of these peptides and their derivatives are also summarized.